A Recent Review on Chemiluminescence Reaction, Principle and Application on Pharmaceutical Analysis. (26th November 2013) - Fereja, Tadesse Haile; Hymete, Ariaya; Gunasekaran, Thirumurugan
Abstract : This paper provides a general review on principle of chemiluminescent reactions and their recent applications in drug analysis. The structural requirements for chemiluminescent reactions and the different factors that affect the efficiency of analysis are included in the review. Chemiluminescence application in immunoassay is the new version for this review. Practical considerations are not included in the review since the main interest is to state, through the aforementioned applications, that chemiluminescence has been, is, and will be a versatile tool for pharmaceutical analysis in future years.